Eco-Friendly Fabrication and Chemical Profiling of Termite Wing-Derived Novel Chitosan-Silver Nanoparticles with Antibacterial and Antibiofilm Potentials - Saravanan, Karunakaran; Manickam, Raja; Shanmugam, Karthik; Arulselvan, Palanisamy; Deepankumar, Shanmugamprema (Asian Journal of Chemistry, 2026)
This study reports a sustainable route for preparing chitosan-capped silver nanoparticles (CSAg NPs) using chitosan obtained from termite wings (Odontotermes obesus) through a straightforward one-pot synthesis. The method enabled the reduction of Ag+ ions to metallic silver under mild conditions, producing stable nanoparticles without using harsh reagents. UV-visible spectroscopy verified that nanoparticles were formed as a result of the reaction of chitosan with silver nitrate, which exhibited a surface plasmon resonance (SPR) peak at 425 nm. The X-ray diffraction data suggested that the resulting material was crystalline in nature; however, Fourier transform infrared (FTIR) spectra demonstrated that the hydroxyl and amino functionalities on the chitosan molecules were present and thus may have played a role in the stabilisation of the nanoparticles produced. Further analysis of morphology and element composition was carried out by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy to further verify the particle structure and presence of silver in the samples. The synthesised CSAg NPs exhibited excellent antibacterial activity at a concentration of 200 µg/mL, with inhibition zones of 15.3 ± 1.52 mm against Streptococcus mutans and 16.6 ± 1.52 mm against Streptococcus sobrinus. In addition, the nanoparticles demonstrated strong antibiofilm action against both oral infections. The prepared CSAg NPs showed pronounced antibiofilm activity against oral pathogens, indicating their potential application in controlling dental infections. The use of termite-wing-derived chitosan as a precursor for nanoparticle fabrication is reported here for the first time, offering a novel, environmentally friendly strategy for developing antimicrobial materials targeting biofilm-associated oral diseases.